2022
DOI: 10.1155/2022/6426763
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Development of Novel Bio‐mulberry‐Reinforced Polyacrylonitrile (PAN) Fibre Organic Brake Friction Composite Materials

Abstract: Natural fibre reinforcement is used in important sectors such as medical, aerospace, automobile, and many other fields. Many articles have reported that natural fibre has the potential to replace synthetic fibres. Natural fibre reinforcement has given good results as a brake friction material. It has already been proven that asbestos causes lung cancer and mesothelioma in brakes. Many people died from the effects of asbestos. According to the World Health Organization’s trending brake report, this material lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Another study based on the estimation of frictional behaviour of a brake pad material fabricated from waste tire dust showed prominent displays of being a reliable alternative [4]. Shells of cocoa beans [5] and bio-composites [6] also proved to be effective in terms of their wear-resisting abilities in several studies. Bahari et.…”
Section: Introductionmentioning
confidence: 99%
“…Another study based on the estimation of frictional behaviour of a brake pad material fabricated from waste tire dust showed prominent displays of being a reliable alternative [4]. Shells of cocoa beans [5] and bio-composites [6] also proved to be effective in terms of their wear-resisting abilities in several studies. Bahari et.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%